KETEPATAN IDENTIFIKASI KESULITAN PESERTA DIDIK DAN ANALISIS RANCANGAN BIMBINGAN EFEKTIF DI SEKOLAH - Takdirmin; Andi Aryunida Batari; Nur Fahera; Sofyan Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study highlights the importance of accuracy in identifying students’ learning difficulties and designing effective guidance services in schools. Findings reveal that internal factors such as low motivation, academic anxiety, and cognitive differences, along with external factors including family support, teaching methods, and limited school facilities, significantly contribute to academic barriers. Accurate diagnosis of learning difficulties through observation, interviews, and diagnostic instruments enables interventions tailored to students’ needs. Furthermore, the analysis of guidance program design emphasizes that services based on students’ actual needs can enhance motivation, foster positive character development, and strengthen social skills. These findings underline the necessity of a holistic approach and supportive educational systems to optimize students’ academic potential and personal growth